Enhancing epidemiological knowledge of Botryosphaeriaceae in Mexican vineyards - RANGEL-MONTOYA, Edelweiss A.; CANDOLFI-ARBALLO, Ofelia; OBRADOR-SÁNCHEZ José Abraham; VALENZUELA-SOLANO, Cesar; HERNANDEZ-MARTINEZ, Rufina (Phytopathologia Mediterranea, 2024)
Grapevine cultivation in Mexico is important, especially in the states of Baja California and Coahuila, which are the main wine production regions in the country. Grapevine trunk diseases (GTDs) impact productivity and cause substantial economic losses, with Botryosphaeria dieback being one of the most destructive. This disease is caused by fungi in the Botryosphaeriaceae, including species of Botryosphaeria, Diplodia, Lasiodiplodia, and Neofusicoccum. To date, Lasiodiplodia spp. are the primary Botryosphaeriaceae fungi reported in Mexico. The present study aimed to enhance the epidemiological knowledge of Botryosphaeriaceae in Mexican vineyards. Samples from grapevine plants exhibiting disease symptoms were collected from the states of Baja California and Coahuila. Of a total of 37 Botryosphaeriaceae isolates, six species were identified: Neofusicoccum parvum, N. australe, N. vitifusiforme, Botryosphaeria dothidea, Diplodia corticola, and D. seriata. Neofusicoccum parvum isolates were the most virulent, but were less virulent than previously reported Lasiodiplodia spp. The optimum growth temperatures for N. parvum and B. dothidea were from 28 to 30°C, but 25°C for D. seriata, N. vitifusiforme, and N. australe isolates. Only D. seriata isolates recovered growth when transferred to room temperature after exposure to 37°C or 40°C. This report is the first identification of B. dothidea and N. parvum as causative agents of Botryosphaeria dieback in the vine-growing regions of Mexico.